Adhesion Properties between Microphase-Separated Segmented Polyurethane and Corona Treated PP Substrate - Kongpun, Teerin (Naresuan University Journal: Science and Technology (NUJST); Vol 25 No 2 (2017): April - June 2017, 2017)
Segmented polyurethane elastomers (SPUEs) were prepared using two different polymer glycols, namely poly (oxytretamythylene) glycol (PTMG) and poly (butylene adipate) glycol (PBA). In addition, polypropylene substrate (PP-Substrate) act as a non-polar substrate and PP substrates have limitations to their adhesion properties due to their non-polar nature and low surface tension. Corona treatment can make a free radical on the surface. Effect of polyether- and polyester polyols on microphase-separated structure and on adhesion properties of SPU pressed with corona treated PP substrate was evaluated using swelling, differential scanning calorimetry (DSC), T-peel testing, single lap shear testing and contact angle measurement. In PTMG-SPU, the crosslink density was largely low whereas the degree of swelling was high. On the other hand, the crosslink density and degree of swelling of PBA-SPU exhibited high and low, respectively. This result means that the crosslink density affects the mobility of hard segment to pack itself correctly to form hard domains. The amount of crosslinks should lead to a structural change in SPU surface as the hard segment structure, thus it also changes in the adhesion properties of SPU based different polymer glycols. It is noteworthy that the carbonyl group in PBA-SPU for adhesion, based T-Peel test and single lap shear test results, have good adhesive properties. The glass transition temperature (T g ), Melting temperature of soft segment (T m,S ) and melting temperature of hard segment (T m,H ) of PBA-SPU was higher than that of PTMG-SPU. The microphase separation of the polyether based SPU (PTMG-SPU) was stronger than that of polyester based SPU (PBA-SPU). It was easily expected that the polar hard segment component can be diffuse to the top surface of PTMG-SPU. Keywords: Corona treatment, Surface free energy, Segmented polyurethane
Keywords: Corona treatment, Surface free energy, Segmented polyurethane